Malaria attributable fractions with changing transmission intensity: Bayesian latent class vs logistic models - Mwai, Kennedy; Nkumama, Irene Nailain; Thairu, Amos; Mburu, James; Odera, Dennis; Kimathi, Rinter; Nyamako, Lydia; Tuju, James; Kinyanjui, Samson; Musenge, Eustasius; Osier, Faith (Malaria journal, 2022)
Asymptomatic carriage of malaria parasites is common in high transmission intensity areas and confounds clinical case definitions for research studies. This is important for investigations that aim to identify immune correlates of protection from clinical malaria. The proportion of fevers attributable to malaria parasites is widely used to define different thresholds of parasite density associated with febrile episodes. The varying intensity of malaria transmission was investigated to check whether it had a significant impact on the parasite density thresholds. The same dataset was used to explore an alternative statistical approach, using the probability of developing fevers as a choice over threshold cut-offs. The former has been reported to increase predictive power.